Pathogenesis and Rehabilitation Therapy of Aging-Related Cognitive Impairment - GONG Weijun (康复学报)
The incidence of aging-related cognitive impairment has been increasing year by year with the increase of the average life expectancy of the global population, which seriously affects the daily quality of life and mental health of the elderly, and has become a clinical hotspot of wide social concern. This study summarized the definition, risk factors, pathogenesis, diagnosis, rehabilitation assessment and rehabilitation treatment methods of aging-related cognitive impairment, in order to provide a theoretical basis for early diagnosis and precise prevention and treatment of aging-related cognitive impairment. Among them, the pathogenesis of aging-related cognitive impairment mainly includes oxidative stress, synaptic plasticity, epigenetic modification and chronic inflammation. Rehabilitation assessment mainly includes neuropsychological assessment [Mini-Mental State Examination (MMSE), Montreal Cognitive Assessment (MoCA), Wechsler Memory Scale (WMS) and Loewenstein occupational therapy cognitive assessment (LOTCA)], electrophysiological and neuroimaging examination [electroencephalogram (EEG), functional magnetic resonance imaging (fMRI) and magnetic resonance spectroscopy (MRS)]. Rehabilitation treatment methods mainly include drug therapy (acetylcholinesterase inhibitors and N-methyl-D-aspartate receptor antagonists) and non-drug therapy [cognitive training, exercise training, multimodal cognitive training, traditional Chinese medicine and traditional medical techniques, other therapies (lifestyle interventions and music therapy)].